Políticas de ensino superior, graduação em terapia ocupacional e o ensino de terapia ocupacional social no Brasil - Pan, Livia Celegati (2014)
The higher education policies recently adopted in Brazil, especially the Support Program to Restructuring and Expansion Plans of Federal Universities REUNI and the National Program of Reorientation of the Professional Training in Health Pró- Saúde, have promoted the expansion of courses and vacancies in Federal Institutions of Higher Education (IFES) and has redirected the formation of professionals those work in health area respectively, with implications also for the training of occupational therapists.This study aimed to understand the deployment process and the folding downof the REUNI and Pró-Saúde with relation to undergraduate courses in occupational therapy from IFES and its Political Pedagogical Projects, tracing a general overview of how the teaching of occupational therapy has being developed in those institutions, since when those Programs have been implemented. Also it searched to identify the explicit discussion in undergraduate of the social occupational therapy in particular, through curriculum contents. For the realization of this study, besides the composition of the theoretical reference for analysis in the scope of the higher education and occupational therapy in Brazil, it was realized interviews with coordinators of undergraduate courses in occupational therapy from IFES in operation between 2012 and 2013, and the documentary survey of their political-pedagogical projects. By the systematization and analysis of data it was found that the REUNI had a big impact to the area, having been fundamental to the expanding process of public vacancies in occupational therapy, mainly to regions of the country those didn´t have this undergraduate degree in a public institution of higher educationyet. On the other hand, the Pro-Saúde wasn´t a substantial presence in most of the courses studied and their repercussions in the area were indirects. In a general way, the undergraduate courses in occupational therapy from IFES are in line with the National Curricular Guidelines, however, curricular flexibility promoted by them, as the normative imposed for courses deemed of the health area, have influenced the teaching of occupational therapy and reflected negatively on subareas those are not only of the health sector, such as social occupational therapy. The contents of this subarea are little inserted in the curriculum of courses and the most of them it is not specifically discussed. It is concluded by the need for rediscussion inside the occupational therapy of the guiding elements of undergraduate education especially in reference to the defense, or not, of a professional with generalist profile.